Accuracy of Computer-Guided Implantology with Pilot Drill Surgical Guide: Retrospective 3D Radiologic Investigation in Partially Edentulous Patients - Federico Gelpi; Nicolò Modena; Alessandro Poscolere; Fabio Bernardello; Lorena Torroni; Daniele De Santis (Medicina, 2023)
Background and Objectives: Implant placement with static navigation enables the reaching of a correct position of implants from an anatomical and prosthetic point of view. Different approaches of static navigation are described in the scientific literature, and the pilot-guided approach is one of the least investigated. The aim of the present study is the evaluation of the accuracy of implant insertion using a pilot drill template. Materials and Methods: Fifteen partially edentulous patients, requiring an implant rehabilitation of at least one implant, were enrolled. Pre- and post-operative low-dose CTs were acquired to measure the differences between final positions of implants and virtually planned ones. Three linear discrepancies (coronal, apical, and depth), two angular ones (bucco-lingual and mesio-distal), and the imprecision area were evaluated. Correlations between accuracy and rehabilitated jaws, sectors, and implant length and diameters were also analyzed. Results: Forty implants were inserted in fifteen patients using pilot drill templates. Mean coronal deviation was 1.08 mm, mean apical deviation was 1.77 mm, mean depth deviation was −0.48 mm, mean bucco-lingual angular deviation was 4.75°, and mean mesio-distal one was 5.22°. The accuracy was statistically influenced only by the rehabilitated jaw for coronal discrepancy and sectors and implant diameter for bucco-lingual angular deviations. Conclusions: The pilot drill template could represent a predictable solution to obtain a correct implant placement. Nonetheless, a safety margin of at least 2 mm should be respected during implant planning to prevent damages to anatomical structures. Therefore, the tool is helpful in order to prosthetically drive the implants; still, great attention must be paid in fully relying on this procedure when approaching dangerous structures such as nerves and vessels.